2004
DOI: 10.1111/j.1432-1033.2004.04098.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of two new IgE‐binding proteins from the yeast Malassezia sympodialis with sequence similarities to heat shock proteins and manganese superoxide dismutase

Abstract: Malassezia sympodialis is an opportunistic yeast that colonizes human skin and may induce IgE and T cell reactivity in patients with atopic eczema/dermatitis syndrome (AEDS). Previously, we have cloned and expressed six recombinant allergens (rMala s 1 and rMala s 5 to rMala s 9) from this yeast. By combining high throughput screening and phage surface display techniques, 27 complete and partial IgE-binding clones of M. sympodialis have been identified. Here we enlarged the panel of recombinant M. sympodialis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 50 publications
0
63
0
Order By: Relevance
“…Its antioxidant activity protects the skin against the toxicity of oxygen-related radicals and the enzyme is up-regulated by UV exposure, mechanical trauma [20], and in the lesional skin of patients with AE [11]. The 2 proteins chosen are of particular interest, since sensitization to Mala s 11 has been observed in AE patients [7] and hMnSOD has been suggested to be self-reactive in these patients [11]. The results of the present study suggest that Mala s 11 can affect the immune system through DCs with the up-regulation of the maturation marker CD83, the co-stimulatory molecules CD40, CD80, CD86 and HLA-DR necessary for antigen stimulation to T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its antioxidant activity protects the skin against the toxicity of oxygen-related radicals and the enzyme is up-regulated by UV exposure, mechanical trauma [20], and in the lesional skin of patients with AE [11]. The 2 proteins chosen are of particular interest, since sensitization to Mala s 11 has been observed in AE patients [7] and hMnSOD has been suggested to be self-reactive in these patients [11]. The results of the present study suggest that Mala s 11 can affect the immune system through DCs with the up-regulation of the maturation marker CD83, the co-stimulatory molecules CD40, CD80, CD86 and HLA-DR necessary for antigen stimulation to T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Mala s 11 has a high degree of sequence homology to manganese superoxide dismutase (MnSOD) from Homo sapiens (50%) and Aspergillus fumigatus (56%) [7]. It has been observed that MnSOD derived from H. sapiens is able to bind IgE in sera from asthmatic patients allergic to A. fumigatus [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 BiP also shares a high degree of sequence homology to heat shock protein 70 (Hsp70), which has been reported as an allergen in many fungi. 45,46 Oxygen evolving enhancer protein was a prominent allergen in our analysis; however, there are no studies in the literature that currently report this protein to be an allergen.…”
Section: Discussionmentioning
confidence: 70%
“…These data can explain why fungi-allergic patients show reactivity to several fungal species [22]. Furthermore, there is evidence that the IgE against M. sympodialis protein manganese superoxide dismutase can cross-react with a corresponding human protein, leading to autoreactivity in patients with AD [23]. The majority of studies involving yeasts and AD patients focus mainly on the members of the genus Malassezia [24][25][26][27].…”
mentioning
confidence: 99%